2022
DOI: 10.1109/access.2022.3149893
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of Energy-Efficient Magnetorheological Fluid Bypass Damper for Prosthetics Limbs Using a Fuzzy-Logic Controller

Abstract: Walking behaviour in amputees with lower-limb loss is absent from shock-absorbing properties. A damper can be used to reduce the impact of ground reaction force (GRF) during heel strikes. Magnetorheological fluid (MRF) damper is deemed the best option for this application as it includes the advantages of both passive and active dampers. An enhanced MRF damper is essential in supplying the appropriate current and damping force levels. Therefore, an energy-efficient design is required to prolong the battery life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…The controller determines the amount of force required to reduce the effect of the force experienced during an impact (Nordin et al, 2018). The results indicated that implementing the F-PID controller (PID with fuzzy) in the system provides better performance in reducing vibrations than the PID controller (Nordin et al, 2018(Nordin et al, , 2022. Due to the limitations of PID, in most MRF applications, PID control strategies are combined with other control schemes (Choi et al, 2016).…”
Section: Kneementioning
confidence: 99%
“…The controller determines the amount of force required to reduce the effect of the force experienced during an impact (Nordin et al, 2018). The results indicated that implementing the F-PID controller (PID with fuzzy) in the system provides better performance in reducing vibrations than the PID controller (Nordin et al, 2018(Nordin et al, , 2022. Due to the limitations of PID, in most MRF applications, PID control strategies are combined with other control schemes (Choi et al, 2016).…”
Section: Kneementioning
confidence: 99%
“…The distinctive characteristics of MR fluids have found application in various devices, where the absence of moving parts is an important advantage (Eshgarf et al, 2022; Zhu et al, 2012). Some examples include light-weight, semi-active damping devices for miscellaneous applications (Jiang et al, 2022), damping systems for ground vehicles with high dynamic range and low stroking load (Bai et al, 2013), or even MR dampers used in prosthetic limbs (Nordin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Due to the large yield stress and damping force of MRF, it has been widely used in the field of damping, for instance, MRF dampers with double annular damping gap, 17 Integral MRF dampers, 18 MRF dampers for FUZZY-PID controller. 19 However, micron-scale MRF tend to aggregate and precipitate with poor stability.…”
Section: Introductionmentioning
confidence: 99%